KALIGRAFI ISLAM SEBAGAI ALAT TERAPI ART THERAPY BAGI PASIEN GANGGUAN DEPRESI - Shafwan Aidinal Ma’arif (NIHAYAH: Journal of Islamic Studies, 2025)
This study investigates the effectiveness of Islamic calligraphy as an adjunctive therapy for patients with mild to moderate depression within a culturally and spiritually contextualized Islamic framework. Utilizing a mixed-methods approach, the study involved 30 participants divided into two groups: an experimental group (Qur’anic calligraphy therapy) and a control group (general art therapy). The intervention included 12 sessions of writing Qur’anic verses of hope using the khat naskh style combined with mindfulness techniques. Quantitative results showed a 40% greater reduction in PHQ-9 scores in the calligraphy group compared to the control (p<0.01). Neurophysiological data revealed a 25% increase in alpha wave activity during calligraphy sessions compared to free drawing. Symbolic analysis of artwork indicated dominant use of blue and gold, associated with tranquility and spirituality. In-depth interviews revealed that 73% of participants cited the meaning of the verses as a key factor in mood improvement, and some developed personalized “calligraphy journals” as a form of self-healing. These findings suggest that Islamic calligraphy offers an effective, culture-sensitive psychospiritual intervention for Muslim patients. The study recommends integrating calligraphy modules into mental health clinics and training counselors as Islamic art therapists. It also highlights future research opportunities in exploring digital calligraphy interventions using tablets and stylus for Gen Z Muslims.